Effects of mucilage concentration at different water contents on mechanical stability and elasticity in a loamy and a sandy soil. (5th November 2021) - Rosskopf, Ulla; Uteau, Daniel; Peth, Stephan
Abstract: Mucilage released by plant roots affects hydrological and mechanical properties of the rhizosphere. The aim of this study was to disentangle the effects of the factors mucilage and soil moisture on a range of soil mechanical parameters in a sand and a loam. Both substrates were homogenised and filled into cylinders at bulk densities ( ρ b ) of 1.26 and 1.47 g cm −3 for loam and sand, respectively. Chia seed ( Salvia hispanica L.) mucilage concentrations of 0, 0.02, 0.2 and 2 g dry mucilage kg −1 dry soil were tested at four different gravimetric water contents in loam ( θ g = 0.34, 0.19, 0.14 and 0.09 g g −1 ) and three in sand ( θ g = 0.20, 0.06 and 0.04 g g −1 ). To quantify the influence of water content on the effect of mucilage on mechanical soil properties, two sets of samples were prepared, one for a micro penetrometer test, the other to measure bulk soil properties. Penetration tests were performed at 120 mm h −1 using a universal testing machine with a high‐precision sensor equipped with a penetrometer conus resembling a root. Mechanical energies were determined by calculating the area of the time–force curves. The energy required for a root to grow in a loam at permanent wilting point was decreased from 0.31 J in the control to 0.26 J in the 2 g kg −1 mucilage treatment, whereas it increased from 0.05 J in the control to 0.08 J at the highest water content. Pre‐compression stress ( σ pc ), compression index ( C c ), swelling index ( C s ) and elasticity index were determined with a confined uniaxial compression test. σ pc was increased by addition of mucilage in both substrates whereas the response on compressibility and elasticity was specific to substrate and water content. Here mucilage had a stronger impact on sand—the substrate with lower initial compressibility and elasticity. We conclude that the effect of mucilage on soil mechanical properties and subsequently on plant growth depends on the combined response of substrate and water content. Highlights: The influence of soil moisture on the mechanical effects of mucilage concentration was examined. Mucilage decreased the energy required for root growth in a loam at the permanent wilting point. Higher mucilage concentrations increased compressibility and elasticity in sand. Effect of mucilage on mechanical parameters depends on interaction between substrate and moisture.